Ultrasound Elastography 2020
DOI: 10.5772/intechopen.88004
|View full text |Cite
|
Sign up to set email alerts
|

Elastometry Indices of Unchanged Liver in Healthy Children

Abstract: Two hundred healthy children aged 3-18 years were included in the study to determine liver stiffness indices by means of shear wave elastometry. The difference is significant when we compared shear wave velocity in children aged 3-6 years, on the one hand, and in children aged 7-18 years, on the other (p = 0.001). Liver stiffness indices in boys and girls were not different. As a result, liver stiffness indices in children in various age groups have been obtained, which can be recommended as normal ones for pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 13 publications
0
1
0
Order By: Relevance
“…In clinical practice, this factor seems to be especially relevant for individual follow-up of patients, which should be performed with a similar setup as the baseline examination to reduce spurious variability in results. A slight age dependency of liver elasticity has been shown using VCTE (3.4 kPa in ages 1–5 years to 4.1 kPa in ages 12–18 years) [ 79 ] and 2-D SWE (4.9 kPA in ages 3–6 years and 5.2 kPa in ages 12–18 years [ 80 ]. A study including 128 healthy children showed that height was the only significant predictor of shear wave speed (positively correlated) [ 74 ].…”
Section: Liver Stiffnessmentioning
confidence: 99%
“…In clinical practice, this factor seems to be especially relevant for individual follow-up of patients, which should be performed with a similar setup as the baseline examination to reduce spurious variability in results. A slight age dependency of liver elasticity has been shown using VCTE (3.4 kPa in ages 1–5 years to 4.1 kPa in ages 12–18 years) [ 79 ] and 2-D SWE (4.9 kPA in ages 3–6 years and 5.2 kPa in ages 12–18 years [ 80 ]. A study including 128 healthy children showed that height was the only significant predictor of shear wave speed (positively correlated) [ 74 ].…”
Section: Liver Stiffnessmentioning
confidence: 99%